Association of Risk Factors with Insulin Resistance/Sensitivity Biomarkers among Manufacturing Industrial Workers - Kalahasthi Ravibabu (Journal of Krishna Institute of Medical Sciences University, 2020)
Background: The association of risk factors with the insulin resistance/sensitivity biomarkers were assessed in population based studies but not in industrial settings. Aim and Objectives: This study assessed the association of risk factors with the Insulin Resistance (IR) and Insulin Sensitivity (IS) biomarkers among industrial workers. Material and Methods: A cross-sectional study. IR and IS biomarkers were assessed in 137 (94 male and 43 female) industrial workers. Serum levels of glucose, Triglyceride (TG) and High Density Lipoprotein–Cholesterol (HDL-C) were measured using diagnostic kit. Serum level of insulin was quantified using ELISA method. IR and IS biomarkers were compared with gender, age, and occurrence of smoking, alcohol consumption, waist circumference, body mass index, hypertension, diabetes, elevated triglyceride, low HDL-C and metabolic syndrome among industrial workers. Results: The levels of IR biomarkers: Homeostatic Model Assessment of Insulin Resistance (HOMA-IR), computerized model of IR (HOMA2-IR), β-cell function (HOMA-%B), TG/HDLC, insulin: glucose, Metabolic Score of Insulin Resistance (METS-IR) and Triglyceride/ Glucose (TyGI) were increased and IS biomarkers: Quantitative Insulin Sensitivity Check Index (QUICKI) and HOMA- % S were decreased in workers with the exhibits of risk factors. Apositive and significant association was noted between HOMA-IR and HOMA2-IR (r=0.988; P<0.01), HOMA-%B (r=0.554; P<0.01), TG/HDL-C (r=0.362, P<0.01), Insulin: Glucose (r=0.862; P<0.01), METS-IR (r=0.457; P<0.01) and TyGI (r=0.477; P<0.01). A negative and significant association was observed between HOMA-IR and QUICKI (r=-0.976; P<0.01) and HOMA-%S (r=-0.988; P<0.01). The association of risk factors with the IR and IS biomarkers was assessed by using linear multiple regression analysis. The results indicated that 86% of risk factors influenced by METS-IR and followed by 66% TyGI, 57% TG/HDL-C, 49% HOMA-IR, 37% HOMA-%S, 34% QUICKI, 30% HOMA2-IR, 16% HOMA-%B and 16% of Insulin: Glucose. Conclusion: The IR markers such as METS-IR, TyGI and TG/HDL-C were mainly influenced by risk factors compared to other biomarkers of IR/IS.